Intracerebral transplantation of autologous adipose‐derived stem cells for chronic ischemic stroke: A phase I study. (21st October 2021) - Chiu, Tsung‐Lang; Baskaran, Rathinasamy; Tsai, Sheng‐Tzung; Huang, Chih‐Yang; Chuang, Ming‐Hsi; Syu, Wan‐Sin; Harn, Horng‐Jyh; Lin, Yi‐Chun; Chen, Chun‐Hung; Huang, Pi‐Chun; Wang, Yi‐Fen; Chuang, Chi‐Hsuan; et al.
Abstract: Current therapy does not provide significant benefits for patients with chronic stroke. Pre‐clinical studies suggested that autologous adipose‐derived stem cells have benefits for the treatment of chronic stroke. This Phase I open‐label study was conducted to demonstrate the safety and efficacy of autologous adipose‐derived stem cells (GXNPC1) in chronic stroke. Three patients with chronic stroke were treated with stereotactic implantation of autologous adipose‐derived stem cells (1 × 10 8 cells). The primary endpoints of safety evaluation included adverse events, over a 6 months post‐implantation period. The secondary endpoints included improvements in neurological functions. Evolutional change of brain parenchyma was also followed with magnetic resonance imaging (MRI). All three participants improved significantly at 6 months follow‐up. The extent of improvement from pre‐treatment was: National Institutes of Health Stroke Scale improved 5‐15 points, Barthel Index: 25–50 points, Berg balance scale 0–21 points and Fugl‐Meyer modified sensation 3–28 points. All three patients had signal change along the implantation tract on MRI one month after surgery. There is no related safety issue through 6 months observation. Clinical measures of neurological symptoms of these patients with chronic stroke improved at 6 months without adverse effects after implantation of autologous adipose‐derived stem cells (GXNPC1), which might be correlated with post‐implantation changes on brain MRI. Clinical Trial Registration‐URL: https://clinicaltrials.gov/ct2/show/NCT02813512?term=ADSC&cond=Stroke&cntry=TW&draw=2&rank=1 Unique identifier: NCT02813512.